Chapter 5 Fusion of Horizons Antonio's Melancholy - Money and Credit in The Merchant of Venice - Jiao, Min (Taylor & Francis, 2023)
"Fusion of Horizons: Interdisciplinary Perspectives on The Merchant of Venice" integrates new horizons into the reading of The Merchant of Venice, particularly horizons about the culture of credit. It delves into the changing nature of money, credit, and debt in the emerging capitalist era in relation to religious and ethnic issues in order to disclose the cause of Antonio's melancholy. It is the argument that the gradual commercialization, materialization and symbolization of an individual in the nascent capitalist era fill Antonio with inexpressible melancholy. Shakespeare, through Antonio, manifests his concerns and worries about a future society preoccupied with money and symbolic economy.